Sulforaphane ameliorates high-fat diet-induced spermatogenic deficiency in mice†. Issue 1 (20th April 2019) - Mu, Yang; Yin, Tai-lang; Huang, Xiao-xuan; Hu, Xue; Yin, Lu; Yang, Jing
Abstract: Sulforaphane (SFN), a dietary isothiocyanate that is mainly found in cruciferous vegetables, possesses anti-oxidative and anticancer activity and modulates inflammation. However, little is known about the role of SFN in obesity-related male reproductive defects. The present study aimed to investigate the effects of SFN on high-fat diet (HFD)-induced male spermatogenic impairment and further clarify the possible underlying mechanisms. In this study, 8-week-old mice were randomly divided into four groups. Mice were fed a normal diet or an HFD with or without SFN supplementation. Sulforaphane was subcutaneously injected at a dose of 0.5 mg/kg 5 days/week for 4 weeks beginning 8 weeks after initiation of the HFD. The results demonstrated that SFN could protect against HFD-induced reproductive dysfunction in male mice. Moreover, SFN also improved reproductive ability, as demonstrated by an increased pregnancy rate and decreased embryo resorption rate in comparison to the corresponding HFD group. We also observed a decrease in apoptosis and an attenuation of endoplasmic reticulum (ER) stress after SFN treatment. In vitro studies of mouse and human sperm samples also revealed that SFN protects against the palmitic acid-induced reduction in sperm viability and motility by inhibiting ER stress in an AMP-activated protein kinase (AMPK)-dependent manner. AMPK-dependent ER stress attenuation by SFN was further confirmed using AMPK knockout mice. Taken together, these data show that SFN protects against HFD-induced male reproductive dysfunction by inhibiting ER stress and apoptosis. These findings may be helpful for identifying new therapeutic methods to treat male infertility.